Efficient attack detection and data aggregation algorithm - Hong-bing CHENG; Chun-ming RONG; Xiao HUANG; Skjalg EGGEN; Qing-kai ZENG (Tongxin xuebao)
An efficient algorithm of attack detection and data aggregation for wireless multimedia sensor networks based on the previous work was proposed.The proposed algorithm concludes the action trait of sensor nodes from their attribute vectors without any prior knowledge,at the same time;it was scalable and could be applied in large scale net-works.The simulation results show that the proposed algorithm can detect the attacks action more accurate than other technologies,and can make data aggregation efficiently.At the same time,the proposed algorithm can make the wireless multimedia sensor networks secure and reduce communication flow so that it will save a lot of resources in wireless mul-timedia sensor networks.